COST VARIATION STUDY OF ANTIEPILEPTIC DRUGS AVAILABLE IN INDIA - Wagle, Laxman; M, Kumara Swammy; M, Kumara Swammy (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To list the available dosage forms in different strengths of various antiepileptic drugs marketed in India. To calculate percentage cost variation of individual formulation of drug manufactured by different companies. To evaluate percentage cost variation of drug due to different dosage forms and formulation of the same drug by cost/defined daily dose (DDD) method and to identify less costlier antiepileptic. Methods: Cost of a particular drug being manufactured by different companies, in the same strength and dosage forms was obtained from Current Index of Medical Specialtiesâ€ 2015 and Indian Drug Reviewâ€ September 2015. The difference in the maximum and minimum price of the same drug manufactured by different pharmaceutical companies and the percentage cost variation was calculated. The price was measured in Indian rupess (cost/DDD units). The percentage cost variation of drug due to different formulations was also calculated using minimum and maximum cost/DDDThe cost of each drug were also estimated as mean cost per DDD considering different formulation cost. Results: The prices of total 11 drugs available in 12 different dosage forms and 65 formulations were reviewed. Except Zonisamide, all drugs (for 31 different formulations) showed more than 100% cost variation. Levetiracetam (conventional 250 mg tablet) showed a maximum of 1034.09% and carbamazepine (dispersible 100 mg tablet) showed minimum cost variation of 2.09%. Levetiracetam formulations showed high (3125.74%), and Topiramate formulations showed less (11.7%) variation in cost to achieve same DDD. The topiramate was expensive, and phenobarbital was cheaper based on cost/DDD only. Conclusion: There was a high-cost variation of antiepileptic drugs. It shows need for conducting pharmacoeconomic analysis. The prescribers and patient should be educated about drug prices. The government has to change the pricing policy of medicine. Keywords: Antiepileptics, Cost/defined daily dose, Cost variation.